Chronic neutrophilic leukaemia: 14 new cases of an uncommon myeloproliferative disease. Issue 11 (1st November 2002) - Böhm, J; Schaefer, H E
Abstract : Background: Chronic neutrophilic leukaemia (CNL) is a distinct BCR/ABL negative myeloproliferative disorder of elderly patients characterised by sustained neutrophilia and splenomegaly. The bone marrow shows expansion of neutrophilic granulopoiesis, without excess of myeloblasts. To date, only 129 cases of CNL have been reported in the literature. Aims: To report the findings from a large group of 14 new cases of CNL, consisting of eight women and six men (mean age, 64.7 years). Methods: A review of the 14 new cases of CNL and the investigation of BCR/ABL translocations in these patients. Results: Three quarters of the patients died within two years after diagnosis, mostly as a result of severe cerebral haemorrhage. Two younger patients were successfully treated with allogeneic bone marrow transplantation or interferon, which resulted in haematological remission for years. Conclusion: CNL is a rare myeloproliferative disease mostly taking a fatal clinical course, despite the presence of mature neutrophils as leukaemic cells in the blood. Thus, it is important to recognise CNL to develop appropriate therapeutic strategies for affected patients.